2018
DOI: 10.29202/nvngu/2018-4/1
|View full text |Cite
|
Sign up to set email alerts
|

Petrographic research on stone tools from the megalithic cult site of Tokivske-1

Abstract: Purpose. Determination of the stone raw materials resource base used by the populations of various historical epochs, who left their monuments in the territory of the stationary megalithic cult site in the village of Tokivske, Apostolove Raion, Dnipropetrovsk Oblast, Ukraine. Methodology. The research was performed using the method of comparative petrographic analysis of stone artefacts and rocks from natural exposures in thin sections. findings. Twelve artefacts were analyzed: eight of the Bronze Age, one of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Data were ob tained on the technology of mining, preparation, and melting of ore. Using mineralogical and petrographic methods, stone tools used in the production process were investigated, most of which are not of local origin, but have analogues among raw materials mined in the Bronze Age on the territory of the Ukrainian shield [9,10]. The latter fact testifies to the distant trade relations of the Kartamysh inhabitants.…”
Section: Methodsmentioning
confidence: 99%
“…Data were ob tained on the technology of mining, preparation, and melting of ore. Using mineralogical and petrographic methods, stone tools used in the production process were investigated, most of which are not of local origin, but have analogues among raw materials mined in the Bronze Age on the territory of the Ukrainian shield [9,10]. The latter fact testifies to the distant trade relations of the Kartamysh inhabitants.…”
Section: Methodsmentioning
confidence: 99%
“…The authors already carried out a petrographic study of stone artefacts from Tokivske-1, found during the first five years of excavation (Nikitenko, 2018). However, new discoveries in the territory of the complex led to the need in revising the role of the studied monument, particularly as a metal processing center of the Bronze Age.…”
mentioning
confidence: 99%